Assessment of efficacy of single dose acetylsalicylic acid over a 24-hour period - Reşat Mehmet Baha; Çağdaş Özdöl; Sadi Güleç; Çetin Erol (KARE Publishing, 2015)
OBJECTIVE: Acetylsalicylic acid (ASA) has a half-life of less than 30 minutes in the human body. This study aimed to test whether the effects of a single dose of ASA wane over a 24- hour period due to the daily release of new reactive blood platelets into the bloodstream. METHODS: The study included 30 patients (10 female and 20 male, mean age: 62.8+-9.0). Each took a single dose of 300 mg enteric coated ASA orally. Platelet aggregation was determined using VerifyNow® Aspirin kits immediately prior to intake, and at 12 and 24 hours following intake. Laboratory parameters such as serum CRP and CBC were also examined before ASA intake. Patients were included irrespective of routine ASA and/or clopidogrel use. RESULTS: Aspirin reaction unit (ARU) values were lower than 550 at 24 hours after drug intake in 26 (86.7%) patients. Values lower than 550 indicate therapeutic range of ASA on platelet function. Two (6.7%) patients were found to be responsive to ASA at 12 hours after intake, but unresponsive at 24 hours. Aspirin resistance was found in another 2 (6.7%) patients. CONCLUSION: Although ASA was found to be effective on platelet inhibition over a 24-hour period in most of the patients, there was a considerable number who were resistant to ASA, and who had developed unresponsiveness to ASA by the end of 24 hours. There is evidence in the literature regarding the clinical importance of ASA resistance, but the importance of loss ASA's effectiveness during a day warrants further studies.